Advising patients to increase fluid intake for treating acute respiratory infections. - Guppy, M; Mickan, S; Mar, D (2005)
BACKGROUND: Acute respiratory infection is a common reason for people to present for medical care. Advice to increase fluid intake is a frequent treatment recommendation. Attributed benefits of fluids include replacing increased insensible fluid losses, correcting dehydration from reduced intake and reducing the viscosity of mucus. However, there are theoretical reasons for increased fluid intake to cause harm. Anti-diuretic hormone secretion is increased in lower respiratory tract infections of various aetiologies. This systematic examination of the evidence sought to determine the benefit versus harm from increasing fluid intake. OBJECTIVES: To answer the following questions. (1) Does recommending increased fluid intake as a treatment for acute respiratory infections improve duration and severity of symptoms? (2) Are there adverse effects from recommending increased fluids in people with acute respiratory infections? (3) Are any benefits or harms related to site of infection (upper or lower respiratory tract) or a different severity of illness? SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library Issue 2, 2005), MEDLINE (1966 to July Week 1, 2005), EMBASE (1974 to Week 29, 2005), Current Contents (current 5 years) and CINAHL (1982 to July week 3 2005). Reference lists of articles identified were searched, and experts in the relevant disciplines were contacted. SELECTION CRITERIA: Randomised controlled trials (RCTs) that examined the effect of increasing fluid intake in people with acute respiratory infections. DATA COLLECTION AND ANALYSIS: Each author assessed the identified studies to determine eligibility for inclusion. MAIN RESULTS: No RCTs assessing the effect of increasing fluid intake in acute respiratory infections were found. AUTHORS' CONCLUSIONS: There is currently no evidence for or against the recommendation to increase fluids in acute respiratory infections. The implications for fluid management in acute respiratory infections have not been studied in any RCTs to date. Some non-experimental (observational) studies report that increasing fluid intake in acute respiratory infections may cause harm. RCTs need to be done to determine the true effect of this very common medical advice.